APPLICATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE CONDITIONS OF THE PRACTICE-ORIENTED APPROACH OF PROFESSIONAL TRAINING OF FUTURE TEACHERS OF ELEMENTARY CLASSES - Albina Venerovna Sadikova (Galaxy International Interdisciplinary Research Journal, 2021)
The article reveals the use of information and communication technologies in the context of a practice-oriented approach to the professional training of future primary school teachers. The ole of information and communication technologies in optimizing the educational process and improving the quality of education is considered.